Історичні аспекти інтродукції та селекції витких троянд роду Rosa L. у світі та Україні - Buidina, T.O.; Rozhok, O.F.; Chizhankova, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to explore the history of the introduction and selection of climbing roses of the genus Rosa L. in the world and Ukraine, find out the main periods in the history of cultivation of these plants and identify the most important introduction and selection centers. Material and methods. In the process of studying literary sources historical-scientific method was used. Problem-chronological method provided a sequence of presentation of the material. Results. In the history of the introduction of roses, one of the main factors was the attraction to the culture of wild agrestic rosehip species. This process lasted quite a long time (five centuries), but had very positive consequences for the future development of roses and climbing particulars. The most intense exchange of plants occurred in the period of the great geographical discoveries, starting from the XV century. Long before New Era, roses were cultivated in China and India, in countries of the Middle East and Asia Minor. From there, with the flourishing of trade in the ancient period they penetrated into ancient Greece, and in subsequent centuries into the countries of Western Europe. The introduction of Sino-Chinese plants into the botanical gardens of Europe began in the first half of the XVIII century and reached its peak in the 40s–60s of the XIX century. During the XVII–XIX centuries and at the beginning of the XX century, significant amount of wild rose was brought from Southeast Asia, but the most important ancestors of climbing roses that originate from Asia are: R. chinensis Jacq., R. lucieae Franch. & Rochebr. ex Crep., R. multiflora Thunb., R. moschata Herrm. Based on the analysis of the history of the selection of climbing roses in the world, three main periods can be distinguished: the last is the period of prehistory by 1875; the present – from 1875 to 1967, the modern – from 1967. Intensive selection work with roses in Europe began in the XVIII century. Wide-scale work was carried out in France, Germany, England, Ireland, the Netherlands, Denmark. The revolution in the formation of a new assortment of climbing roses produced R. multiflora and R. wichuriana Crep. Barbier (France) breeders in Jackson, Perkins and Brownelló in the USA achieved particularly significant results in the selection of Vihurayan roses in France. M.A. Gartvis, M.D. Kostetskiy, V.M. Klimenko, Z.K. Klimenko, K.I. Zykov made a significant contribution to the development of domestic breeding. As a result of the tremendous work done by the breeders, a worldwide assortment of climbing roses has been created, which now numbers thousands of varieties. Conclusions. The early periods of the introduction of climbing roses in the world (the initial and the period of intensive introduction) are analyzed. It was revealed that R. moschata has long been used in climbing gardens in the Middle East countries, and in the United States (since 1759) the East Asian species R. laevigata. During the period of active involvement of Sino-Chinese plants R. multiflora (1868) was introduced into Europe’s botanical gardens. According to results of studying the history of culture and the experience of introduction of climbing roses of the genus Rosa in Ukraine, the main introduction centers have been identified. The study of the history of the selection of climbing roses in the world and in Ukraine and the analysis of the stages of the selection process with climbing roses made it possible to identify outstanding breeders who have made significant contributions to the development of selection and the creation of varieties of climbing roses.